2011
DOI: 10.1007/s00210-011-0672-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of morphine in regulation of cancer cell growth

Abstract: Morphine is considered the “gold standard” for relieving pain and is currently one of the most effective drugs available clinically for the management of severe pain associated with cancer. In addition to its use in the treatment of pain, morphine appears to be important in the regulation of neoplastic tissue. Although morphine acts directly on the central nervous system to relieve pain, its activities on peripheral tissues are responsible for many of the secondary complications. Therefore, understanding the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 91 publications
6
91
0
1
Order By: Relevance
“…Reports have simultaneously shown the archetypal opiate morphine is able to both inhibit the growth of cancer cells as well as to stimulate them in vitro. As some of these cancer cell lines express relatively low levels of the opioid receptors (8), the effects on growth may be independent of them. Furthermore, as both the pro-and anticancer effects have been seen in animal model systems with intact immunity, it has been postulated that morphine may affect the immune response (9), although, this remains inconclusive (10).…”
Section: Introductionmentioning
confidence: 99%
“…Reports have simultaneously shown the archetypal opiate morphine is able to both inhibit the growth of cancer cells as well as to stimulate them in vitro. As some of these cancer cell lines express relatively low levels of the opioid receptors (8), the effects on growth may be independent of them. Furthermore, as both the pro-and anticancer effects have been seen in animal model systems with intact immunity, it has been postulated that morphine may affect the immune response (9), although, this remains inconclusive (10).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic pain in cancers, such as breast and prostate, are primarily treated with opioids, which over prolonged treatment durations lead to decreased efficacy, increased tolerance, and even promotion of tumor growth [20,51]. Moreover, the precise neurobiological mechanisms underlying this pain remain unknown, which poses a serious challenge for the development of efficacious analgesics.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have shown the pro-apoptotic action of morphine on cancer cells by different mechanisms including inhibition of NF-κB via nitric oxide [23,24] whereas other studies have shown inhibition of apoptotic processes via p53, a key factor in programmed cell death [25][26][27]. These findings are somewhat conflicting with data showing an inhibitory effect of morphine tumor cell proliferation in vitro [28][29][30][31].…”
Section: Mechanism Favoring Type Of Anesthesia and Cancer Recurrencementioning
confidence: 99%